Modifiable risk factors of respiratory infections in children´s homes and social gardens of the municipality of San José de Cúcuta - París Pineda, Olga María; Castillo Ortega, Nohora Liliana; Dávila, Andrea Paola; Angel Sandoval, Cindy Johanna; Calvo Betancur, Víctor Daniel (Universidad y Salud, 2013)
Introduction: The WHO considers acute respiratory infection as a public health problem. It is a prevalent childhood disease and it has been shown that when children enter to a kindergarten, the infectious episodes as well as the possibility of complications and the risk of death increase. Objective: To identify some modifiable risk factors of acute respiratory infection present in state kindergartens. Methods: A cross-sectional observational study was made. All the children’s homes and social gardens of the municipality of San Jose de Cucuta were chosen in 2011. Two instruments were applied, which allowed describing modifiable risk factors in the institutions. Results: These institutions nurse a pediatric population of 2497 people, from which 49.6% are girls. Differences in modifiable risk were highlighted when comparing the two types of institutions, such as physical infrastructure and staff caring for the child. They presented similar risks such as faults in washing hands and little collaboration of the family to maintain the care of the sick child at home. Conclusion: The risk factors presented in the institutions require attention as well as the implementation of prevention programs. However, these risks can also be found at home and they must be dealt with from there.